Fractional Langevin Equations with Nonseparated Integral Boundary Conditions. (19th August 2020) - Hilal, Khalid; Ibnelazyz, Lahcen; Guida, Karim; Melliani, Said
Abstract : In this paper, we discuss the existence of solutions for nonlinear fractional Langevin equations with nonseparated type integral boundary conditions. The Banach fixed point theorem and Krasnoselskii fixed point theorem are applied to establish the results. Some examples are provided for the illustration of the main work.